Fish parasitofauna checklist in two areas of southern Sinaloa, Mexico: collaborative academic work effort 2022-2024 - López-Ceseña, J. Ángel Gibrian (2025)
Fishing is a vital and productive activity worldwide, contributing significantly to food security and food production. Sinaloa, Mexico, is a fishing city with a diverse range of crustacean and fish species that inhabit its coastal waters. However, little is known about its parasitofauna, a crucial aspect for preventing zoonotic diseases. The objective of this study was to compile a list of fish parasitofauna from two coastal areas in southern Sinaloa during two years of student service in the Bachelor's degree programs in Fisheries and Aquatic Sciences, Facultad de Ciencias del Mar (FACIMAR), Universidad Autónoma de Sinaloa, Mazatlán, México. During the 2022-2024 period, 290 fish were collected from two different regions of southern Sinaloa: Mazatlán and Walamo, as part of academic and community service activities. The fish species collected were “chihuil” (Bagre panamensis, Gill, 1863), ”pajarito” (Hyporhamphus naos, Collette & Bruce, 2001), “lisa” (Mugil cephalus, Linnaeus, 1758), “dorado” (Coryphaena hippurus, Linnaeus, 1758), “sierra” (Scomberomorus sierra, Jordan & Starks, 1895), “mojarras” (Eucinostomus currani, Zahuranec, 1980 and Eucinostomussp., Baird & Girard, 1855), sharks (Sphyrna sp., Rafinesque, 1810), “agujón” (Tylosurus pacificus, Steindachner, 1876), “chopa” (Spondyliosoma cantharus, Linnaeus, 1758) and “burrito” (Orthopristis chalceus, Günther, 1864). The fish were transported in ice-filled coolers. Ectoparasites and endoparasites from six taxonomic groups were identified: eight copepods (Crustacea), five monogeneans, four cestodes, six digeneans (Platyhelminthes), three nematodes (Nematoda), and, one acanthocephalan (Acanthocephala), present in various habitats, including muscles, brains, gills, and intestines. The high number of parasites found were copepods in all sampling areas. The participation and collaboration of students during community service internships are particularly noteworthy, especially in promoting research that will undoubtedly contribute to their academic training.